Group Flow States of Intergenerational Networks Within Age-Friendly Academic Settings - Flor, Alexander G. (International Journal on Open and Distance e-Learning, 2020)
This paper proposes a theoretical framework for investigating group flow within intergenerational networks. The framework is based on preliminary observations of intergenerational engagement among faculty members of an online open university. In describing, explaining and predicting group flow dynamics, the framework borrows heavily from autopoietic theory (Maturana & Varela, 1987), systems theory (Bateson, 1972), and flow theory (Csikszentmihalyi, 1990; Kotler & Wheal, 2017). A flow state is described as “an optimal state of consciousness where we feel our best and perform our best” (Csikszentmihalyi, 1990, p.5) Technically defined, it is the mental state of operation in which a person performing an activity is fully immersed in a feeling of energized focus, full involvement, and enjoyment in the process. Flow states may be experienced not only among individuals but among groups, the latter termed as group flow or communitas (Ibid). Autopoiesis, on the other hand, carries much intergenerational resonance since it is concerned with the renewal, regeneration, and evolution of living systems. A university, constituting different generations of academics, would represent such a living system engaged in a continuing effort of self-renewal and self-reinvention. Oftentimes, age, generational, and ideological chasms are wide enough to result in tensions that lead to system dysfunction even within open and online settings. During group flow states, intergenerational differences are diminished in a manner conducive to system renewal and reinvention.